Delegation of decision rights and capital reallocation: Evidence from US municipalities - Asghar, Nauman; Obloj, Tomasz (Strategic Management Journal, 2025)
Abstract Research Summary We investigate the role of organizational structure in influencing internal capital reallocations. Despite the importance of flexible capital reallocation, empirical evidence suggests remarkably high levels of stability in these decisions. Adopting a behavioral perspective, we focus on information processing demands faced by boundedly rational decision‐makers as an antecedent of such decision patterns. We argue, and provide evidence, that centralization of decision rights, which increases information processing demands, results in lower levels of capital reallocations, compared with decentralized structures. Empirically, we explore the causal effect of centralization on reallocation, leveraging an exogenous variation in decision rights among Illinois state municipalities. Additional analyses provide further evidence that a likely mechanism explaining our findings is that of decentralization reducing information processing load on decision‐makers. Managerial Summary Drawing on data from municipalities in the State of Illinois, we show that the delegation of decision rights for resource allocation leads to a higher reallocation among municipal functions, compared with a centralized decision‐making structure. Organizations often face resource constraints, and they must make trade‐offs when allocating resources to competing projects. In such an environment, resource reallocation process can be paramount to achieving strategic goals. Given that managers have a choice in designing decision‐making arrangements for allocation of resources, they can decide to (de)centralize resource allocation process according to the desirability of reallocation. Our findings indicate that centralization of decision‐making leads to a greater information processing burden faced by managers, affecting the magnitude of resource reallocation.